Surface modification of mild steel using a combination of laser and electrochemical processes - Speidel, Alistair; Lutey, Adrian Hugh Alexander; Mitchell-Smith, Jonathon; Rance, Graham A.; Liverani, Erica; Ascari, Alessandro; Fortunato, Alessandro; Clare, Adam T. (Elsevier, 2016)
Traditional methods for achieving hierarchical surface structures include highly specified, deterministic approaches to create features to meet design intention. In this study microstructural alteration was undertaken using laser apparatus and secondary texturing was achieved via succeeding electrochemical processes. Electrochemical jet machining (EJM) was performed on mild steel subjected to laser pre-treatment using power densities of 4167 and 5556 W/cm2 with pulse durations from 0.3 - 1.5 seconds. Results show that in combination, laser pre-treatment and EJM can alter the exposed surface textures and chemistries. Here, machined surface roughness (Sa) was shown to increase from approximately 0.45 µm for untreated surfaces to approximately 18 µm for surfaces subjected to extreme laser pretreatments. After pre-treatments materials were characterised to appraise microstructural changes, shown to be martensite formation, reinforced by complementary simulation data, and significant increases in observable hardness from approximately 261 HV for the asreceived material to over 700 HV after pre-treatment. The greater hardness was retained after EJM. Exposed martensitic lath structures at machined surfaces are shown to be partially responsible for surface roughness increases. The surfaces were explored with energy dispersive X-ray spectroscopy (EDS) and Raman spectroscopy demonstrating changes in apparent surface chemistry. This analysis revealed increasing oxide formation at the surface of the pre-treated EJM surface, a further contributory factor to surface roughness increases. This new process chain will be of interest to manufacturers seeking to control surface morphology for applications including micro-injection mould/die manufacture. While demonstrated here for steel similar mechanisms are exploitable in other material systems. A new technique has been demonstrated, resulting from the models and processes presented to couple laser and electrolyte jet processing for complex surface preparation.